2017
DOI: 10.1111/ajco.12749
|View full text |Cite
|
Sign up to set email alerts
|

Phase II study of celecoxib with docetaxel chemoradiotherapy followed by consolidation chemotherapy docetaxel plus cisplatin with maintenance celecoxib in inoperable stage III nonsmall cell lung cancer

Abstract: The activity of this regimen has been demonstrated. Treatment-related toxicity was substantial. The role of celecoxib in addition to CRT could not be demonstrated in this study because of the small number of patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 29 publications
0
7
0
Order By: Relevance
“…Solid tumors possess heterogeneous structures and a microenvironment regulated by a complex signaling pathway network, such that the combination therapy strategies using different drugs to act on multiple oncotargets have a better chance to improve the therapeutic outcome. , It is well documented that chronic inflammation is one of the common features of cancer, where cyclooxygenase-2 (COX-2) and a pro-inflammatory mediator, COX-2-derived prostaglandins 2 (PGE 2 ), play critical roles in the maintenance of tumor viability, growth, metastasis, and angiogenesis. , On the other hand, chemotherapy often induces the upregulation of COX-2, PGE 2 , and anti-apoptotic genes ( e . g ., Bcl-2), upon which the malignant cells acquire resistance to chemotherapeutic agents. , Previous studies have shown that nonsteroidal anti-inflammatory drugs (NSAIDs), for example, celecoxib (CXB), could inhibit not only the inflammatory COX-2/PGE 2 pathway to influence the hallmarks of cancer but also the anti-apoptosis genes to reduce chemoresistance. ,, Therefore, a combination therapy using a chemotherapeutic drug and a NSAID could be a powerful strategy to alter the characteristic pro-inflammatory environment of the tumor and sensitize cancer cells to chemotherapy. , Although the combination therapy strategy using COX-2 inhibitors and chemotherapeutic drugs has initiated several clinical trials, anti-inflammatory drugs as adjuvants for chemotherapy in clinical studies are usually administered as free form, making it hard to achieve a desirable synergistic anticancer effect and was even reported to likely lower the anticancer activity of chemotherapeutic drugs due to two drug interactions . Additionally, the long-term administration of free NSAIDs may result in severe side effects…”
mentioning
confidence: 99%
“…Solid tumors possess heterogeneous structures and a microenvironment regulated by a complex signaling pathway network, such that the combination therapy strategies using different drugs to act on multiple oncotargets have a better chance to improve the therapeutic outcome. , It is well documented that chronic inflammation is one of the common features of cancer, where cyclooxygenase-2 (COX-2) and a pro-inflammatory mediator, COX-2-derived prostaglandins 2 (PGE 2 ), play critical roles in the maintenance of tumor viability, growth, metastasis, and angiogenesis. , On the other hand, chemotherapy often induces the upregulation of COX-2, PGE 2 , and anti-apoptotic genes ( e . g ., Bcl-2), upon which the malignant cells acquire resistance to chemotherapeutic agents. , Previous studies have shown that nonsteroidal anti-inflammatory drugs (NSAIDs), for example, celecoxib (CXB), could inhibit not only the inflammatory COX-2/PGE 2 pathway to influence the hallmarks of cancer but also the anti-apoptosis genes to reduce chemoresistance. ,, Therefore, a combination therapy using a chemotherapeutic drug and a NSAID could be a powerful strategy to alter the characteristic pro-inflammatory environment of the tumor and sensitize cancer cells to chemotherapy. , Although the combination therapy strategy using COX-2 inhibitors and chemotherapeutic drugs has initiated several clinical trials, anti-inflammatory drugs as adjuvants for chemotherapy in clinical studies are usually administered as free form, making it hard to achieve a desirable synergistic anticancer effect and was even reported to likely lower the anticancer activity of chemotherapeutic drugs due to two drug interactions . Additionally, the long-term administration of free NSAIDs may result in severe side effects…”
mentioning
confidence: 99%
“…Several clinical trials have begun for these combination drugs; it is difficult to achieve a desirable synergistic anticancer effect because anti-inflammatory drugs are generally administered in free form in clinical studies [168][169][170][171]. In addition, the long-term administration of nonsteroidal anti-inflammatory drugs in free form can cause serious side effects [172].…”
Section: Spatiotemporal Drugs Release By Matrix Metalloproteinase-2 (mentioning
confidence: 99%
“…Consolidation ST was seemingly first attempted some 26 years ago and has witnessed many transformations since then. During the initial years of its use, many studies used the same drugs given in both concurrent and consolidation phases of the treatment [ 6 , 7 , 8 , 9 , 10 , 11 , 12 , 13 , 15 , 16 , 17 , 19 , 21 , 22 , 25 , 28 , 29 , 32 , 33 , 34 , 35 , 36 , 38 , 39 , 42 , 44 , 45 , 49 , 53 , 58 , 59 , 62 , 64 , 66 , 67 , 68 , 70 ] while many subsequent studies used different drugs (“switch” approach) [ 14 , 18 , 20 , 23 , 24 , 26 , 30 , 41 , 43 , 47 , 49 , 52 , 60 , 61 ] based on the assumption that consolidation drugs may be more effective and less toxic when differ...…”
Section: Introductionmentioning
confidence: 99%
“…Regardless of the type and the number of drugs as well as the duration of the consolidation phase of the treatment, the evaluation of the patient response after the concurrent RT-ST phase of the treatment has been considered an important moment in the decision-making process, in which patients should continue the treatment with the consolidation phase [ 73 , 74 , 75 ]. While some studies did not undertake it [ 6 , 21 , 29 , 32 , 42 , 49 , 52 , 53 , 55 , 61 , 72 ], some did but continued with consolidation ST in all patients [ 7 , 8 , 11 , 15 , 16 , 17 , 18 , 19 , 20 , 30 , 31 , 37 , 38 , 40 , 44 , 45 , 48 , 51 , 56 , 59 , 60 , 62 , 66 , 67 , 68 ], while others mandated that the consolidation phase proceeds only in non-progressive disease (non-PD) patients [ 10 , 12 , 13 , 14 , 22 , 23 , 24 , 26 , 35 , 36 …”
Section: Introductionmentioning
confidence: 99%